Development of Differentiated Learning Strategies with an Inclusive Approach at Madrasah Aliyah in Deli Serdang - Mardianto; Nasution, Wahyudin Nur; Supriatin (Universitas PGRI Yogyakarta, 2026)
This research aims to develop a differentiated learning strategy that incorporates an inclusive approach in Islamic jurisprudence to enhance student learning outcomes at Madrasah Aliyah Negeri 1 Deli Serdang. This research employed the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model, developed by Robert M. Branch. The research findings of this study demonstrate the effectiveness and practicality of implementing a differentiated learning strategy with an inclusive approach in Islamic jurisprudence (Fiqh). Learning activity increased across trials, with a score of 2.67 in the first trial (practical with minor revisions) and rising to 3.67 in the second trial (very practical). Most notably, the strategy was found to be effective in enhancing student learning outcomes, as indicated by the results of a statistical paired t-test, where the calculated t-value (17.86) exceeded the critical t-value (2.045). Furthermore, the normalized gain (N-Gain) score reached 0.587, reflecting a moderate level of improvement. Keywords: learning strategy, differentiated learning, inclusive approach